Study of Sea Surface Temperature (SST), Does It Affect Coral Reefs? - Eghbert Elvan Ampou; Masita Dwi Mandini Manessa; Faisal Hamzah; Nuryani Widagti (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
HighlightEffect of sea surface temperature on coral reefsCorrelation with NOAA and AQUA MODIS satellite imagery dataSea water quality analysisThe adaptability of coral reefsAbstractThis research aims to identify the influence of Sea Surface Temperature (SST) to coral disease and bleaching using MODIS-Aqua data from 2003-2009 and NOAA Coral Reef Watch data. Field-data collection on coral disease and bleaching was carried out in Bunaken National Park, Wakatobi National Park, and Raja Ampat, in August, October, and November 2009, respectively. The presence of coral disease and bleaching was observed by using time-swim method. A prevalence formula was used to calculate the percentage of coral disease and bleaching colonies. The range of mean SST value from each location: Bunaken from 26.84-31.45oC, Wakatobi from 26.09-31.95oC and Raja Ampat from 27.72-31.36oC. There is an influence of SST anomaly on the presence of dis- ease and coral bleaching. During 2003-2019, the highest SST anomaly that could increase the risk of the coral bleaching phenomenon was found in 2010. Coral disease and bleaching were found at locations with high SST anomaly, low nitrate and available phosphate. However, high SST anomalies were not a main cause of coral disease and bleaching. In many locations in Indonesia, mass-bleaching has occurred and the ability of coral adaptation is the main key in dealing with this phenomenon.